Evaluation of the nitrosamine hypothesis of gastric carcinogenesis in precancerous conditions. - Hall, C N (1986)
A 24 hour gastric aspiration study was carried out on nine Polya gastrectomy, eight pernicious anaemia, and nine matched control subjects. Intragastric pH, bacteria, nitrite, and N-nitroso compounds were assessed half hourly whilst ambulant and hourly when in bed. Both total and nitrate reducing bacterial counts were positively related to pH (chi 2 = 279.3; p less than 0.001), as was nitrite concentration (F = 19.1; p less than 0.0001). By contrast, total (F = 40.6; p less than 0.0001) and stable (F = 257.4; p less than 0.0001) N-nitroso compound concentrations were negatively related to pH. Clear differences in these gastric juice factors were not apparent between matched control and either pernicious anaemia, or Polya gastrectomy because the Polya gastrectomy and matched control groups were heterogeneous for gastric acidity. Thus, although eight of eight pernicious anaemia subjects were hypoacidic (defined as intragastric pH greater than 4 for greater than 50% of both daytime and night time periods), only five of nine Polya gastrectomy and two of nine matched control subjects were hypoacidic. When subjects were rearranged into hypoacidic (n = 15) and acidic (n = 11) groups, bacterial counts (p less than 0.01) and nitrite concentrations (p less than 0.01) were higher, whereas N-nitroso compounds tended to be lower (NS) in the hypoacidic group. These data suggest that, although hypoacidity predisposes to bacterial overgrowth and nitrite generation, it does not enhance nitrosation. Instead, this is maximal at low pH, suggesting chemical rather than bacterial nitrosation, contrary to the nitrosamine hypothesis of gastric carcinogenesis.